Innovation of Hiwalah al-Haq, Wakalah, and Ijarah Hybrid Contracts at BPRS: Alternative Receivables Collection Services Based on Sharia Ethics - Syukron Suwardi; Agung (Mabahits Al-Uqud, 2025)
Communities, especially micro businesses, are often faced with difficulties in liquidating bad receivables, which ultimately triggers a personal liquidity crisis. Conventional solutions in the form of using debt collector services often violate sharia ethics and moral principles. This research aims to formulate a conceptual model of innovative products in Sharia People's Financing Banks (BPRS) as an alternative to ethical and sharia-compliant receivables collection services. The methods used are conceptual studies and synthesis of Fiqh Muamalah on the Hiwalah al-Haq, Wakalah bi al-Ujrah, and Ijarah contracts. The results of this study propose a hybrid “Hiwalah Billing Services” model. In this model, BPRS acts as a Muhal ‘Alaih who receives the transfer of the right to claim receivables (Hiwalah al-Haq), as well as as a representative who is authorized to carry out collections professionally and persuasively (Wakalah bi al-Ujrah). BPRS obtains service rewards (ujrah) through an Ijarah contract that is fixed nominally at the beginning, ensuring sharia compliance and avoiding percentage-based practices that are prone to gharar. This model utilizes the capabilities of BPRS in dealing with defaults through a deliberation and restructuring approach, so as to comprehensively realize the noble goals of sharia (Maqasid al-Shari’ah) in the form of property protection (Hifdz al-Mal) and life protection (Hifdz al-Nafs).